Bisguanidinium dinuclear oxodiperoxomolybdosulfate ion pair-catalyzed enantioselective sulfoxidation - Zong, Lili (2018)
Catalytic use of peroxomolybdate for asymmetric transformations has attracted increasing attention due to its catalytic properties and application in catalysis. Herein, we report chiral bisguanidinium dinuclear oxodiperoxomolybdosulfate [BG]2+[(μ-SO4)Mo2O2(μ-O2)2(O2)2]2− ion pair, as a catalyst for enantioselective sulfoxidation using aqueous H2O2 as the terminal oxidant. The ion pair catalyst is isolatable, stable and useful for the oxidation of a range of dialkyl sulfides. The practical utility was illustrated using a gram-scale synthesis of armodafinil, a commercial drug, with the catalyst generated in situ from 0.25 mol% of bisguanidinium and 2.5 mol% of Na2MoO4·2H2O. Structural characterization of this ion pair catalyst has been successfully achieved using single-crystal X-ray crystallography.